Benign fibrohistiocytic tumour of the palate - Nilima Sharma; Mohammad Jaseem Hassan (Wolters Kluwer Medknow Publications, 2020)
Benign fibrous histiocytomas of soft tissue are composed of spindled fibroblasts admixed with secondary elements including histiocytes, foam cells, and inflammatory cells. These tumors occur equally in males and females and most often arise in the dermis and subcutaneous tissues. We report a rare case of benign fibrous histiocytic tumor of the palate with histologic features and immunohistochemical characteristics.